Design of Multifunctional Polarization Waveplates Based on Thermal Phase-Change Metasurfaces - Bo Cheng; Yuxiao Zou; Zihui Ge; Longfeng Lv; Taohua Liang; Kunpeng Zhai; Guofeng Song (Crystals)
The switching function of traditional waveplates necessitates mechanical replacement or the superimposition of multiple waveplates, which gives rise to a complex system and a large volume. We have devised a multifunctional micro-waveplate based on the COMSOL simulation platform (v5.6), which concurrently integrates the compact nature of metasurfaces and the dynamic regulatory features of phase-change materials. When the phase-change material is in the crystalline phase, the metasurface possesses the functionality of a half-waveplate (HWP) and is capable of performing chirality inversion of circularly polarized light within the wavelength range of 1.45 μm to 1.52 μm and 1.56 μm to 1.61 μm. When the phase-change material is in the amorphous phase, the metasurface serves as a quarter-waveplate (QWP) and can achieve the conversion between linear and circular polarization through a 90° phase delay. The phase-change metasurface breaks through the constraint of fixed functions of traditional optical waveplates, facilitating the development of optical systems towards miniaturization, intelligence, and low power consumption and providing a crucial technical route for the next generation of photonic integration and dynamic optical applications.